Relationship between the Handball-Specific Complex-Test and Intermittent Field Test performance in professional players - Hermassi, S.; Hoffmeyer, B.; Irlenbusch, L.; Fieseler, G.; Noack, F.; Delank, K. S.; Gabbett, T. J.; Souhaiel Chelly, M.; Schwesig, R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: We investigated the relationship between the Handball Complex-Test (HBCT) and two selected field performance tests (the repeated sprint ability [RSA], and the Yo-Yo Intermittent Recovery Test) in elite handball players. METHODS: Nineteen handball players (age: 25.7±5.1 years) were drawn from the First Professional German League. The HBCT consists of four activity series (AS): agility parcours, defensive action, sprint (10 m, 20 m) and throw-on-goal parcours; these activities were completed twice, with five active pauses of 30-35 s, and a follow-up of recovery over the subsequent 10 minutes. The RSA comprised 6 x (15+15 m) sprints starting every 20 s; scoring noted best time (RSAbest), total time (RSATT) and decrement (RSAdec). In the Yo-Yo Intermittent Recover, we recorded the total distance covered (TD). Heart rates (HR) were recorded throughout and recovery was assessed for measurements immediately post-test (R0) and 10 minutes after completing the test (R10). RESULTS: A strong correlation was found between HBCT and fastest 10 m and 20 m RSA sprint times (r=0.811, r=0.815, respectively). Also, the HBCT total 10 m and 20 m sprint times showed a strong positive association with RSATT (r=0.70; r=0.63, respectively), and the RSA heart rate post-test was strongly correlated with the HBCT heart rate after round two (r=0.865). CONCLUSIONS: Data from the match-specific HBCT Test shows a strong positive association with other more generic intermittent field test measurements. These observations support the validity of using the generic tests to monitor current fitness and responses to training in team handball players.